Online auction-based resource scheduling in grid computing networks - Lili Ding; Long Chang; Lei Wang (International Journal of Distributed Sensor Networks)
The aim of this article is to introduce a novel auction-based algorithm for grid computing wireless networks and resolve some incompetence with dynamic mechanisms. We develop a reverse online auction method to allocate grid resources, where the grid resource providers arrive dynamically and user broker has to make a multi-attribute decision whether to sell tasks or not before the end of current round. In our approach, a trade-some-with-forecast algorithm is proposed to help the user broker to utilize his forecast ability to allocate the grid resource in an online setting. Furthermore, two reverse online auction-based protocols are presented to demonstrate the resource scheduling in grid computing wireless networks. Experiments show that the reverse online auction-based with forecast protocol has better performance in comparison with the reverse online auction-based protocol. It is efficient in terms of auction stages, user satisfaction, and successful forecast.